ANALYSIS OF THE VALUE – ADDED FOR TAYAN BAUXITE ORE AND CHEMICAL GRADE ALUMINA - Harta Haryadi (Puslitbang tekMIRA, 2016)
Research conducted at PT. ANTAM and PT. ICA (Indonesia Chemical Alumina) Tayan, West Kalimantan was aimed to compare the amount of company value-added from selling the bauxite ore as a raw material and the chemical grade alumina as a processed goods. This research showed that company value added from selling 850.000 tons raw meterial US 8.92 million it consisted of salary and wages of US 692.42 thousand, royalties, CSR and insurance US 473.87 thousand, surveyor services US 150.00 thousand, other services 45.00 thousand, corporate income tax of US 1.64 million, Bank interest US 191.77 thousand. The company profits obtained the US 5, 73 million was. Of the US 8.92 million added value and 850.000 bauxite selling, the increase of total added value was US 10.49 per ton. Selling the chemical grade alumina up to 300,000 tons or equivalent to 850,000 tons provided the value-added to the US 57.24 million that consisted of an increase in revenue salaries and wages to US 3.85 million. 50.75 billion, royalties, CSR and insurance of US 2.49 million, surveyor services and other services US 16.50 million, corporate income tax 10.39 million, Bank interest US 1.21 million and corporate profits to the US 22.00 million. The overall value added from selling the processed goods was US 190.44 per ton. It is indicated that selling the chemical grade alumina provides a greater profit than that of selling the raw material.